4-Bromo-N,N′-diphenylbenzimidamide N′-oxide - Arindam Saha; Daniel Chartrand; Mihaela Cibian; Thierry Maris; Garry S. Hanan (IUCrData)
The title compound, C19H15BrN2O, crystallizes with two similar molecules in the asymmetric unit. The extended structure features dimers linked by pairs of N—H...O and C—H...O hydrogen bonds. The HNCNO moiety of the title compound shows delocalization over the N—C—N part, as evidenced by the similar C—N bond distances.